Insights into the discrepancy between Azadinium spp. and azaspiracid toxins near strategically important aquaculture operations in the west and southwest of Ireland. (5th November 2021) - McGirr, Stephen; Clarke, Dave; Kilcoyne, Jane; Salas, Rafael; Koehler, Henry; Silke, Joe; Touzet, Nicolas
Abstract: Apparent increases in harmful algal blooms worldwide have fostered attempts at mitigating their impacts on the aquaculture industry. The dinoflagellate species Azadinium spinosum has been described as the de novo azaspiracid (AZA) toxin producer of AZA-1 and -2 and been implicated in shellfish poisoning incidents (AZP) around Europe, regularly affecting shellfish mariculture operations. Several species of Azadinium have been confirmed in Irish coastal waters, and routine monitoring has shown disparities between Azadinum spp. cell count estimates in the water column and AZA concentrations in shellfish. A survey of bays on the southwest and west coasts of Ireland, carried out in August 2016, investigated the late summer distribution of Azadinium spp. and AZAs. Molecular analysis of water column samples showed very low levels of Az. spinosum . However, AZAs were found in 44% of samples, including in Az. spinosum negative samples. PCR-DGGE analysis was carried out using Amphidomataceae family specific primers on a selection of Az. spinosum negative, but AZA positive, samples. Subsequently sequenced DNA amplicons showed a high level of similarity with other Azadinium species suggesting that the species-specific molecular assays, in current use for monitoring Azadinium spp., are not capturing the likely greater diversity of the genus in Irish waters. Graphical abstract: Image 1 Highlights: Amphidomataceae detected by qPCR in 97% of samples near two Irish aquaculture sites. Az. spinosum was detected in 28% of samples up to ∼200 cells.L −1 based on qPCR. AZA-1 (up to 465 pg.L −1 ) and AZA-2 (up to 185 pg.L −1 ) were detected at both sites. AZAs detected where Az. spinosum was absent, yet Amphidomataceae were present. DGGE analysis suggests greater Azadinium diversity regionally than known to date.